THE CORRELATION BETWEEN STUDENTS’ VOCABULARY AND THEIR ABILITY IN TRANSLATING ENGLISH TEXT AT THE SIXTH SEMESTER STUDENTS OF UM METRO - Setiawan, Eko Yunius; Sholihah, Lilis (Fakultas Komunikasi, Sastra, dan Bahasa, 2017)
The research aimed to analyse the students? vocabulary mastery, the students? ability in translating English text, and the correlation between students? vocabulary mastery and students? ability in translating English text. This research is a quantitative research by using correlation method. The respondents are sixth semester undergraduate students of Muhammadiyah University of Metro. The technique of the sampling is a total sampling. The applied data collecting techniques are tests of vocabulary mastery and ability in translating English text. The present research used Lilliefors? formula to test the normality of the research and Product Moment Correlation to test the hypothesis. The findings showed positive and significant correlations between students? vocabulary mastery and students? ability in translating English text, it is proven by rxy= 0,507 and is consulted by =0,312 and the result is 0,507 > 0,320. Furthermore, the significant level is gotten = 3,622, this value is compared with  for the degree of error 5% by two tail test and dk= n-2 = 38, so it is obtained = 2.02439. Because of ?0, it can be said that between X and Y variables have a significant correlation. Because the vocabulary mastery and translation ability are correlated with each other, the English learner should increase their mastery of vocabulary to support their ability in translating English text